Some Evidence of the Impact on Non-Wage Labour Cost on Overtime Work and Employment - Laudadio, Leonard; Percy, Michael (Relations industrielles / Industrial Relations, 1973)
Total labour costs can be considered to be a function of the hourly wage, a quasi-fixed component {mainly fringe benefits and training cost) and overtime rate. The theoretical model employee in this paper suggests that an increase in the ratio of quasi-fixed cost to overtime rate leads to an increase in the amount of scheduled overtime work instead of employment. The model, tested with Canadian data, yields statistically significant results.